Geolashon (Teloschistes flavicans), a natural yellow dye from the Peruvian Andes: traditional uses, bioactive extraction, and potential applications (Scientia Agropecuaria, 2023)
Recently, interest in studying pigments from lichens has been aroused due to their bioactive properties and health benefits. The Geolashon (Teloschistes flavicans) is a thousand-year-old lichen from the Peruvian Andes characterized by its yellow filaments, traditionally used by the Peruvian inhabitants as a natural pigment for making handicrafts and medicinal purposes. In this sense, this article aims to compile all the studies on Geolashon as a source of natural yellow pigments, starting from its importance and applications by the Andean population to research on obtaining, characterizing, and properties of its extracts. Although studies on this lichen are limited, it was observed that the obtained from lichen are rich in 3-[1’-(2”,3”-dihydroxy-phenyl)-propyl]-7-hydroxy- chroman-4-one, vicanicin, parietin, other compounds and has antidiabetic, antibacterial, antileukemic, antimicrobial, anticancer and termiticide activity that would be interesting for use in the pharmaceutical, cosmetic, food and agricultural industries, generating added value in the final product. Aspects such as processing, functional properties, and toxicology of the bioactive components of Geolashon must be studied for its correct use.
Keywords: Natural dyes; Bioactive; Lichen dyes; Dye and pigment extraction; Food colors; Non-food dyes